Investigation and quantification of flow unsteadiness in shock-particle cloud interaction. (April 2018) - Hosseinzadeh-Nik, Zahra; Subramaniam, Shankar; Regele, Jonathan D.
Highlights: A shock wave impacting a cloud of dense 2D particles is simulated using the Navier–Stokes equations. A detailed explanation of the flowfield evolution is described for a transverse array and cloud of particles. A quantitative assessment of the flow unsteadiness generated by the interaction is studied with and without the effects of the initial shock wave transience. The vorticity production terms are analyzed to determine where and how the high levels of flow unsteadiness are created. Abstract: This work aims to study the interaction of a shock wave with a cloud of particles to quantify flow unsteadiness and velocity fluctuations using particle-resolved direct numerical simulation (PR-DNS). Three cases are studied, with each case revealing one aspect of the intricate flow phenomena involved in this interaction. The unsteady interaction of a shock wave with a transverse array of particles reveals the origin of unsteadiness under the effect of mutual wave-wave and wave-wake interactions between the particles. In the second case, the interaction of a shock with a particle cloud is studied, with a focus on the interaction of the complex wave system with the vortical structure. A budget analysis of the vorticity equation reveals the sources of strong unsteadiness in the particle cloud. A detailed analysis of the velocity fluctuation and kinetic energy in the fluctuating motion is performed to ascertain the importance of the velocity fluctuations that arise from the strong unsteadiness. An analogous analysis is presented, in the third case, for a gradually-induced flow on the same particle cloud along with a comparison to the shock induced case to assess the impulsive effect of shock on intensity of the fluctuating field statistics.